Angļu valoda izglītības reklāmā - Podziņa, Laura (Latvijas Universitāte, 2009)
Bakalaura darbs ir apskata valodas īpatnības izglītības reklāmā. Izglītības iestādes salīdzinoši nesen ir sākušas sevi reklamēt, tāpēc šis temats iepriekš nav daudz pētīts. Darba mērķis ir izpētīt valodas īpatnības izglītības iestāžu reklāmas materiālos. Kā pētniecības metodes tika izmantota pieejamo teorētisko materiālu izpēte un analīze un izvēlēto izglītības iestāžu reklāmas materiālu diskursa analīze. Pētījuma rezultāti atklāj, ka izglītības iestāžu reklāmas materiāli nesatur daudz reklāmas valodas īpatnību. Atslēgas vārdi: reklāmas valoda, izglītības sektors, reklāmas materiāli

The Bachelor Thesis deals with the characteristics of the language used in education marketing. The education sector has entered the sphere of advertising comparatively recently, that is why this issue has not been researched much. The goal of the Bachelor Thesis is to investigate the peculiarities of the advertising language in promotional materials of educational institutions. The following research methods were used: study and analysis of the available sources on the researched topic and discourse analysis of the selected advertising materials of educational institutions. The results reveal that the promotional materials of educational institutions contain a few peculiarities of the advertising language. Key words: advertising language, education sector, promotional materials
Characteristics of Language Used in Education Marketing
Keywords: Filoloģija